2015
DOI: 10.3390/molecules201019291
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Bioconversion of Ginsenoside Rb1 to Compound K by the Mycelium of Cordyceps sinensis under Optimized Conditions

Abstract: Compound K (CK), a highly active and bioavailable derivative obtained from protopanaxadiol ginsenosides, displays a wide variety of pharmacological properties, especially antitumor activity. However, the inadequacy of natural sources limits its application in the pharmaceutical industry. In this study, we firstly discovered that Cordyceps sinensis was a potent biocatalyst for the biotransformation of ginsenoside Rb1 into CK. After a series of investigations on the biotransformation parameters, an optimal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…The addition of beef extract, yeast extract, peptone and tryptone resulted in the degradation rate of AFB 1 to 74.85 ± 0.13%, 78.51 ± 0.96%, 73.9 ± 0.38%, and 80.56 ± 0.13%, respectively. Carbon is the key nutrient for microbial growth and energy metabolism, and nitrogen is an important component of proteins and nucleic acids (Wang et al, 2015). This result was in contrast to the findings of Mwakinyali et al (2019), who reported that adding carbon or nitrogen can increase the degradation rate of Myroides odoratimimus strain 3J2MO on AFB 1 .…”
Section: Characterization Of B Velezensis Ad8 Afb 1 Degradationcontrasting
confidence: 60%
“…The addition of beef extract, yeast extract, peptone and tryptone resulted in the degradation rate of AFB 1 to 74.85 ± 0.13%, 78.51 ± 0.96%, 73.9 ± 0.38%, and 80.56 ± 0.13%, respectively. Carbon is the key nutrient for microbial growth and energy metabolism, and nitrogen is an important component of proteins and nucleic acids (Wang et al, 2015). This result was in contrast to the findings of Mwakinyali et al (2019), who reported that adding carbon or nitrogen can increase the degradation rate of Myroides odoratimimus strain 3J2MO on AFB 1 .…”
Section: Characterization Of B Velezensis Ad8 Afb 1 Degradationcontrasting
confidence: 60%
“…As a biological hybrid of the larva and parasitic fungus, C. sinensis contains a complex enzymatic system and abundant ingredients with medicinal value (Chen et al, 2017; Hu et al, 2015; Zhong & Xiao, 2009). Several clinical trials regarding the transformation characteristics of C. sinensis have been published (Wang et al, 2015). However, Cordyceps militaris and Panax ginseng (cultivated ginseng, less than 5 years) had been confirmed as new resource food raw materials since 2009 and 2012 respectively, which can be directly used in food production.…”
Section: Introductionmentioning
confidence: 99%
“…Fruitful proceedings have been accomplished through our research, including the establishment and optimization of biotransformation methods for the ample supply of some rare saponins, the discovery and elucidation on new saponin structures that provide potential anticancer agents, and others (Table1). [26][27][28] We also found that several rare or new ginsenosides enhance antitumor immune response in the tumor microenvironment, 25,26 and unpublished data, which will provide some novel medical products for clinical use of ginsenosides.…”
Section: Components and Transformation Of Ginsenosidesmentioning
confidence: 68%